The Relationship between Knowledge of Pregnant Women about Anemia and Prevention of Folic Acid Consumption During Pregnancy - Aryunita (PT Inovasi Pratama Internasional, 2022)
The impact of folic acid deficiency on pregnant women causes birth defects in babies. The purpose of this study was to determine the description of pregnant women's knowledge about the importance of folic acid during pregnancy. This research is descriptive in nature using primary data by distributing questionnaires to each respondent with a total sampling technique of 30 respondents. From the results of this study, it is known that the knowledge of pregnant women about the importance of folic acid in pregnancy, the majority have less knowledge, namely, 15 respondents (50%), based on age the majority have sufficient knowledge, namely 11 respondents (36.66%), with an age group of 20-35 years. , based on education the majority have sufficient knowledge, namely 8 respondents (26.66%) with high school education. Based on parity, the majority have less knowledge, namely 6 respondents (20%) with skundigravida pregnancy, based on occupation, the majority have less knowledge, namely 7 respondents (23.33%) with farmer occupations, based on information sources, the majority have less knowledge, namely 8 respondents (26.66%) with electronic media. Therefore, it can be concluded that there are still many pregnant women who do not know the importance of folic acid on fetal brain development.